THE SGIE ABBREVIATION JOKE IN THE 2024 PRESIDENTIAL AND VICE PRESIDENTIAL DEBATE: A NETNOGRAPHIC STUDY OF TIKTOK POSTS WITH THE HASHTAG #SGIE - Mardhiyyah, Mardhiyyah; Arswendi, Riki (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
The General Election (Pemilu) is a democratic event held every five years by the Indonesian people to elect the President and Vice President. The next election will take place on February 14, 2024. There are three pairs of presidential and vice-presidential candidates who will compete: Pair Number 1, Anies Rasyid Baswedan and Muhaimin Iskandar; Pair Number 2, Prabowo Subianto and Gibran Rakabuming Raka; and Pair Number 3, Ganjar Pranowo and Mahfud MD. As in previous elections, the General Election Commission (KPU) will organize five debate sessions, comprising three for presidential candidates and two for vice-presidential candidates. So far, two debates have been held—one for each candidate type. An intriguing moment occurred during the vice-presidential debate on December 22, 2023, when one candidate asked another about the abbreviation "SGIE," which the latter failed to answer. This sparked a wave of reactions on social media, especially TikTok, where more than 30.4 million posts featured the hashtag #SGIE. Due to this widespread attention, the researchers were motivated to study the phenomenon using a netnographic approach. Data collection was conducted by observing the digital footprints of TikTok users who posted using the hashtag #SGIE.Keywords: SGIE, Tiktok, Netnography